The isolation and characterization of Drosophila yolk protein genes. - Barnett, T.; Pachl, C.; Gergen, J.P.; Wensink, P.C. (Cell, 1980)
We have isolated recombinant DNA clones that contain the genomic sequences coding for the three most abundant proteins in Drosophila eggs, the yolk proteins (YP1, YP2 and YP3). The identity of these cloned genes was established by a two-step procedure. We used the genes to isolate complementary mRNA from total Drosophila RNA; we than showed the in vitro translation products of the isolated mRNAs to be the yolk proteins by comparing their protease digestion products to those of yolk proteins isolated from eggs. An examination of these isolated genes and of their DNA complements in the Drosophila genome showed that each of the three coordinately expressed yolk proteins is encoded by a different single-copy gene. Three genes were cloned; each has a different pattern of restriction endonuclease sites and each appears to be homologous to a different yolk protein mRNA. Southern transfer blots demonstrated that there is only one copy of each gene in the Drosophila genome. Our structural studies have shown that these three genes are not adjacent. In situ hybridization to polytene chromosomes demonstrated, in fact, that the YP3 gene is approximately 1000 kb from the closely spaced YP1 and YP2 genes. Thus, if the coordinate synthesis of the yolk proteins is due to transcriptional control, there must be coordinate control of initiation at two distant sites.